356 National estimates of the prevalence of occupational carcinogen exposure. (11th October 2013) - Fritschi, L; Carey,; Driscoll,; Reid,; Peters, S; Benke,; Glass, D
Abstract : Objectives: To estimate the burden of occupationally-related cancer, the prevalence of occupational exposure to carcinogens is necessary, and this information is not available in most countries. Methods: We surveyed 5023 Australian workers aged 18 to 65 to determine the prevalence of exposure to 38 occupational carcinogens. We developed job specific modules (JSMs) for 57 jobs and industries with questions on the determinants of exposure to the 38 agents and the use of control measures. The answers to the questions were linked by algorithms to assessments of probability and level of exposure within a web-based application (OccIDEAS). Interviewers called randomly-selected phone numbers and asked consenting participants about their current job. If that job had any likelihood of exposure to any of the 38 agents, the interviewer administered the most relevant JSM for that job. The algorithms were then run and the automatic assessments were reviewed by the project co-ordinator, with more complex assessments being referred to occupational hygienists for review. Results: About half of the subjects (n = 2498) were in a job with potential exposure. The most common jobs were construction workers, drivers and health workers. 40% of subjects were exposed to at least one carcinogen, with the most common exposures being solar UV, diesel exhaust and environmental tobacco smoke. We will also present profiles of exposure by industry. For example, almost all carpenters are exposed to wood dust at a high level, while about 80% of painters are exposed to wood dust, half of them at at a high level and half at a low level. Conclusions: The prevalence of exposure to carcinogens at work is quite high and a survey such as ours is useful in pinpointing areas where control of exposure is not adequate. Our findings can be used in calculating the burden of disease from occupational exposures.